The Importance of Stem Based Education in Indonesia Curriculum - Oktian Fajar Nugroho; Anna Permanasari; Harry Firman; Riandi Riandi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2021)
This article describes the importance of the concept of STEM-based education in the Indonesia curriculum. STEM-based education is an educational concept that integrates the concept of education into a single unit between Science, Technology, engineering and Mathematics, the concept of STEM education has been developed in various developing and developed countries today. STEM education does not mean only strengthening educational practice in the fields of education separately, but rather developing an educational approach by integrating several subjects such as science, technology, engineering, and mathematics, by focusing more on the educational process on solving real problems in everyday life. By developing various aspects of attitudes, knowledge and skills as well as increasing critical thinking power and being able to form logical thinking in various fields of knowledge based on the applicable 2013 curriculum.